Stability Study and Simulation of Quadruped Robots with Variable Parameters - Qian Cong; Xiaojie Shi; Ju Wang; Yu Xiong; Bo Su; Wei Xu; Hai Liu; Kuiyue Zhou; Lei Jiang; Weijun Tian (Applied Bionics and Biomechanics)
Walking stability is one of the key problems restricting the development of quadruped robots. Two new kinds of variable parameter quadruped robots with high stability were proposed. The two groups of variable parameter models were applied to quadruped robots with the full elbow joint or elbow joint for front legs and knee joint for back legs, respectively, and the stability of their linear motion under different variable parameters was deeply studied by Recurdyn. The quadruped robots with elbow joint for front legs and knee joint for back legs displayed good antijamming ability to lateral impact. According to the rigid-flexible simulation experiment, the largest force occurred in the knee joint during the movement of the quadruped robot. This provided a theoretical basis for the design of real quadruped robots.